Gambaran Pengelolaan Penyimpanan Obat Di Apotek X Lamongan - Vivian Dwi Putri Anjani; Siti Nur Asiyah; Pemta Tiadeka (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2022)
Apotek X Lamongan is a health service facility that manages supplies in the pharmaceutical sector. Based on preliminary studies that have been carried out, the results show that at Apotek X Lamongan there are often problems in the storage and dispensing of drugs. One of the incidents of wrong drug storage that occurs is not recording the intake and expenditure of drugs. This causes the service to be less than optimal, allegedly because the storage system at the X Lamongan Pharmacy is not fully in accordance with the pharmaceutical service standards at the pharmacy, and there has never been any research on the drug storage system at the X Lamongan Pharmacy. Based on the importance of the impact of drug storage in a pharmacy, it is necessary to evaluate the drug storage system at the X Lamongan Pharmacy. This study aims to evaluate and determine the drug storage system at Apotek X Lamongan. This research is a descriptive observational study by making direct observations of the pharmacy storage system in the form of a checklist and conducting direct interviews with the person in charge of the pharmacy. It shows that in general the drug storage system has a score of 60.41% which is categorized as quite good. The drug storage system includes spatial arrangement with the percentage obtained is 66.67% in the good category, the method of preparation of drugs with a percentage value of 100% in the very good category, recording of stock cards with a percentage value of 0% in the very poor category, and observation of drug quality with a value of 0%. percentage 75% good category. This shows that X Lamongan Pharmacy has not met the storage standards based on Permenkes No. 73 of 2016 and based on BPOM No. 4 of 2018.